Estudo fitossociológico de plantas espontâneas e produção do feijão caupi em sistema de plantio direto em capoeira triturada - Marinho, Tácila Rayene dos Santos (2018)
Cowpea is an important food source for human populations, however, it is a culture affected by ecological factors that can impair its yield as spontaneous plants. The management of these species by the Capoeira milling technology and the use of inoculants for the biological fixation of nitrogen can reduce its interference in the productivity of Cowpea. Thus, the objective of this research was to evaluate the influence of inoculation on spontaneous plants and yield of cowpea in a ground-based capoeira system (mulch technology). The research was conducted from May to June 2017 in the Cristina Alves settlement, Itapecuru Mirim-MA, in an area prepared with grinding of the capoeira for the cultivation of maize succeeded by the culture of Cowpea. The experimental design was in randomized blocks in a 2 x 2 + 2 factorial arrangement, with two cowpea cultivars (BRS Guariba and BR 17 Gurgueia), two microbiological treatments (with and without inoculation) and two additional witnesses with nitrogen fertilization (in cv BRS Guariba and BR 17 Gurgueia), with four replications. Spontaneous plant collections were performed every 10 days (10, 20, 30, 40, 50 and 60 days after the emergence of the crop), with a sampling frame of 0, 5m x 0, 5m randomly released four times in the plot. The plants were collected, identified and dried in greenhouse. The density and dry biomass data of the spontaneous plants were used to determine the phytosociological parameters. At 40 days after plant emergence, nodulation and harvest were evaluated, the number of pods plant-1; The number of pod grains-1 and average mass per grain unit. In the cultivar BRS Guariba, 27 species of spontaneous plants belonging to 12 botanical families were found, whose monocotyledons accounted for 48.1% and eudicotiledons 51.9% of the total species. To cultivate BR 17 gurgueia, 26 species were recorded in ten families, with monocotyledons representing 53.8% and eudicotiledons 46.2% of the total species. In both cultivars, the main family of spontaneous plants was Cyperaceae and the most important spontaneous plants were Vismia guianensis, Cyperus sp. and Scleria Melaleuca. There were no significant effects of the interaction between the cultivars and the microbiological treatments for the number of nodules. The cv. BR 17 Gurgueia presented 22.13 nodules plant-1 while cv. BRS Guariba obtained only 12.53 nodules plant-1. In the inoculation treatment there was the highest number of nodules (24.35 nodules plant-1) than without inoculation and with nitrogen fertilization (witnesses) with a mean of 1.62 nodules plant-1. The cultivars did not differ statistically for the number of pods plant-1 with mean values of 6.87 pod Plant-1, the same occurred for the yield with an average of 1239.05 kg ha-1. The treatments with inoculation and nitrogen fertilization of the cultivars (additional witnesses) recorded the highest values for the number of pods per plant with a mean of 7.79 pods plant-1. For grain yield, the nitrogen fertilization treatment in cv BRS Guariba was superior to the other treatments with 1965, 09 kg ha-1. The triturated Capoeira system promoted a diversity of species in the Cowpea culture whose botanical group of eudicots was predominant in cv BRS Guariba, while in the cultivar BR 17 Gurgueia were monocotyledons. The Cyperaceae family predominates in the cultivation of beans in a crushed capoeira system and the most important species are Vismia guianensis, Cyperus sp. and Scleria Melaleuca. Spontaneous plants do not affect the yield of cowpea (BRS Guariba and BR 17 Gurgueia) in a ground-based capoeira system. The cultivar BR 17 Gurgueia presents higher nodulation, and affinity with the bacteria introduced and the native soil in a crushed capoeira system. The cultivars BRS Guariba and BR 17 Gurgueia are good cultivation options in no-tillage in crushed capoeira.